Fabrication of rainfall simulator for field erosion studies - ARUNADEVI, K.; ARUNKUMAR, S. (Journal of Soil and Water Conservation, 2020)
Due to unpredictable and uncontrollable characteristics of rainfall, it is difficult to assess event-wise soil loss for any location. An effort was made to fabricate a portable and cost economic rainfall simulator for erosion studies. A solid cone nozzle was used in the rainfall simulator to maintain the desired spray pattern by adjusting the pressure and the height of the delivery. By using the flour pellet method, the volume mean diameter of droplet was found to be 2 mm and 2.5 mm for the nozzle height of 2.2 m and 1.5 m above the ground, respectively. Rainfall intensities of 8.1, 10.2, 9.3, 10.5, 13.6 and 19.3 cm/hr were achieved by adjusting pressure rate of 0.5, 1, 1.5, 2, 2.5 and 3 kg/cm2, respectively at a nozzle height of 2.2 m, whereas , 10.6, 12.3, 11.3, 16, 19, 22 cm/hr intensities were achieved at pressure rate of 0.5, 1.5, 2, 2.5 and 3 kg/cm2, respectively at the nozzle height at 1.5 m. It was found that the intensity of rainfall increases with increase in nozzle operating pressure.